GC–MS analyses reveal chemical differences in the leaves of Manihot esculenta Crantz genotypes with different anti-herbivore effects - Barilli, Diandro Ricardo [UNESP]; Budzinski, Ilara Gabriela Frasson [UNESP]; Bronzel Junior, João Luiz [UNESP]; da Silva Bolzani, Vanderlan [UNESP]; Boiça Júnior, Arlindo Leal [UNESP]; Rossi, Guilherme Duarte [UNESP] (Springer Nature, 2021)
Several secondary metabolites are associated with plant resistance against herbivores. Cassava genotypes present a wide variety of metabolites with insecticidal potential, but little is known about the identity of these compounds. The present work was conducted for the identification of insecticidal molecules present in cassava genotypes. To this purpose, we firstly evaluated the development of the generalist herbivore Spodoptera frugiperda (J.E. Smith, 1797) (Lepidoptera: Noctuidae) fed with leaves from six cassava genotypes (IAC-14, IAC-90, IAC-12, IAC-Caapora, Baianinha and MEcu 72). Following bioassays, we measured the levels of two anti-herbivory related groups of compounds (phenolics and steroidal saponins) in all genotypes using colorimetric methods. The metabolic fingerprinting (GC–MS) of three contrasting cassava genotypes selected by their biological interferences over S. frugiperda was performed. The most unsuitable nutritional indices were observed for larvae fed with MEcu 72. Lower reproductive indices were observed for adults in which larval stages were fed with Baianinha or MEcu 72. Steroidal saponin content was similar in all genotypes, but phenolic content was 25% higher in MEcu 72. GC–MS metabolite fingerprinting of MEcu 72, Baianinha and IAC-Caapora resulted in the annotation of 53 metabolites in which 20 presented different relative abundance among the evaluated genotypes. Molecules such as myo-inositol-2-monophosphate, p-coumaric acid, chlorogenic acid, p-hydroxybenzoic acid, octadecadienoic acid and n-hexacosane were more abundant in MEcu 72 or Baianinha than in IAC-Caapora. The possible roles of these molecules in the development of S. frugiperda are discussed.
Keywords: Cassava; Chemical defense; Euphorbiaceae; Gas chromatography; Metabolomics; Spodoptera frugiperda